EFFECT OF PRODUCT INNOVATION AND BRAND AWARENESS ON PRODUCT PURCHASE DECISIONS OF PT. UNILEVER INDONESIA - Wayan Ardani (International Journal of Education, Information Technology, and Others, 2019)
This study aims to determine the effect of product innovation and brand awareness on consumer purchasing decisions for PT. Unilever Indonesia (Community Case Study of Denpasar City). The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study that product innovation had a significant effect on purchasing decisions by 41.5%, the hypothesis test obtained t count> t table or (8,169> 1.986). Brand awareness has a significant effect on purchasing decisions by 43.1%, hypothesis testing obtained t count> t table or (8,434> 1,986). Product innovation and brand awareness simultaneously have a significant effect on purchasing decisions with the regression equation Y = 9.715 + 0.358X1 + 0.409X2. The contribution of the effect was 52.5%, the hypothesis test obtained F count> F table or (51.298> 2,700).